Soil Quality Assessment of Phaeozems and Luvisols from the Kujawy Region (Central Poland) / Ocena cech użytkowych czarnych ziem i gleb płowych rejonu Kujaw - Kobierski Mirosław; Kondratowicz-Maciejewska Krystyna; Kociniewska Katarzyna (Soil Science Annual, 2015)
To assess the soil quality of Phaeozems and Luvisols from Kujawy region (Kujawy-Pomerania Province, Poland), the soil quality indicators such as: content of organic matter and nutrients, as well as bulk density were used. The soils showed similar inherent properties (soil texture, depth to parent material, type of clay) and management practices (tillage, crop rotation, nutrient application). The following properties were determined: bulk density, grain size composition, exchangeable acidity, concentration of available forms of potassium, phosphorus and magnesium, and the content of total organic carbon (TOC) and nitrogen (Nt). The amounts of dissolved organic carbon (DOC) and dissolved nitrogen (DN) were measured in the solution obtained after extraction with 0.004 M CaCl2. The stock of TOCs, Nts and DOCs, and DNs were calculated. The total organic carbon content in surface horizon of Phaeozems was significant higher (13.9-20.1 g·kg-1) than in Ap horizon of Luvisols (8.3-11.0 g·kg-1), which is a consequence of their origin. The stock of organic carbon in Ap horizon fell within 5.89 to 8.49 kg·m2 in Phaeozems and 3.80 to 4.81 kg·m2 in Luvisols. Although Phaeozems demonstrated a significant higher content of TOC, as compared with Luvisols, the amount of dissolved organic carbon was similar in both soil types, which points to a higher share of DOC in the total organic carbon content in Luvisols (up to 17.5% in Et horizon). The amounts of dissolved organic carbon and dissolved nitrogen and their stock do not depend on the type of soils if the management practices are similar.